Emerging strategies for the treatment of advanced small cell lung cancer - Lim, Joline SJ; Collins, Dearbhaile; Yap, Timothy A. (Journal of Thoracic Disease, 2016)
While treatment strategies for non-small cell lung cancer (NSCLC) has made substantial progress in the past two decades with the advent of molecular targeted agents and immune checkpoint inhibitors, advances in the field of small cell lung cancer (SCLC) have been relatively dismal. The mainstay of treatment for advanced SCLC remains platinum-based doublet chemotherapy in the first line setting, with rechallenge of chemotherapy during relapse for platinum-sensitive disease. In the platinum resistant or refractory settings, there are no standard guidelines for treatment, with various phase II studies showing similar response rates (RR) and survival outcomes for different single agent chemotherapies, including topotecan, irinotecan, taxanes and gemcitabine (1).